Gamma Shielding Capabilities of Some Selected Materials Within Ibadan Metropolis - Oluwadare J. AKINDUGBAGBE; Adefope OWOJORI; Emmanuel AGBENYI; Babatunde ADEBO (FUDMA Journal of Engineering and Technology, 2025)
Conventional gamma shielding materials like lead are effective but present limitations related to cost, weight, and fabrication have prompted the need for locally accessed shielding materials. This study evaluates the gamma shielding potential of four locally-sourced materials; sawdust composite, acrylic, clay, and glass readily available within Ibadan metropolis. The elemental composition of each material was determined using ICP-OES and CHNO analyzers. Shielding parameters including linear attenuation coefficient (LAC), half-value layer (HVL), tenth-value layer (TVL), mean free path (MFP), and lead equivalence were estimated theoretically at 661 keV (Cs-137). Experimental HVL values were determined from the spectral response of NaI(Tl) gamma detector as gamma photons from a standard Cs-137 source was attenuated using the locally-sourced materials. From the result of the study, Glass had the highest estimated LAC (0.169 cm⁻¹), followed by clay (0.159 cm⁻¹), sawdust composite (0.153 cm⁻¹), and acrylic (0.095 cm⁻¹). Theoretical HVL values for glass, sawdust composite, clay and acrylic were estimated at 4.10 cm. 4.54 cm, 4.37 cm and 7.31 cm respectively. Experimental HVL values obtained for glass, sawdust composite, clay and acrylic differed from theoretical values by 3.73%, 0.87%, 2.99 % and 11.73%. Glass exhibited the lowest theoretical TVL (13.62 cm) and MFP (5.92 cm), indicating its superior shielding performance. In addition, a total thickness of about 55 cm would be needed to shield the gamma radiation from an active Cs-137 source completely and about 98 cm thickness of acrylic material to shield from the Cs-137 source completely. Due to its density, clay and sawdust may offer more practical alternatives for field use as they are optimally efficient in thicknesses. These findings suggest that locally sourced non-metallic materials can provide viable alternatives to conventional shielding materials in certain gamma radiation environments.